‘Strands in a cable’: effective investigator decision-making using forensic identification evidence in volume crime investigations - Brown, Cheryl (Policing and society, 2024)
Police investigators increasingly make use of forensic science in the investigation of crime. While there is considerable research on case outcomes following the use of forensic identification evidence (fingerprint and DNA evidence), few studies have explored how police investigators use these evidence types in their investigations. This study aimed to examine police investigators’ reasoning processes about the use of forensic identification evidence in volume crimes, such as burglary, to develop a decision-making framework that can be applied to the investigation of such crimes. Twenty-four police officers from three Australian police jurisdictions participated in semi-structured interviews that centred around a case scenario. Data were transcribed verbatim and analysed thematically. The findings highlight that police investigators’ decision-making is influenced by the requirement to meet the rules of evidence. Further, participants’ own experience and mentoring by more experienced colleagues influenced not only the decisions made in a case, but also the development of decision-making skills in the use of forensic evidence more broadly. A decision-making framework is proposed to explain and guide the use of forensic evidence in volume crime investigations. Overall, the findings suggest that the effective use of forensic identification evidence in volume crime investigations requires that police investigators engage actively in the decision-making process. Further research can explore ways to integrate the findings from this research into police practices.